Growth of III-nitrides via sublimation and metalorganic vapor phase epitaxy (Kovine zlitine tehnologije, 1997)
Single crystals of GaN at 1100°C and a triethylgallium flow rate of 26 mmol/min. Approximately ?$10^9$? ?$cm^{-2}$? dislocations, originating from the underlying GaN/AlN interface, were contained in the GaN grown in the window regions. The overgrowth regions contained a very low density of dislocations.
Keywords: nitridi; kristali; sublimacija; Ramanska spektroskopija; luminiscenca; rast kristalov; mikrostruktura